2008
DOI: 10.4097/kjae.2008.55.6.709
|View full text |Cite
|
Sign up to set email alerts
|

The effects of esmolol, esmolol and nicardipine or remifentanil on mean blood pressure, heart rate and recovery in gynecologic laparoscopic surgery

Abstract: Background:The purpose of this study was to compare the effects of esmolol, esmolol and nicardipine or remifentanil on MBP, HR and recovery in gynecologic laparoscopic surgery.Methods: Eighty patients scheduled for gynecologic laparoscopic surgery were randomly allocated to four groups: group C (control group, n = 20); group E (esmolol group, n = 20) received esmolol 1 mg/kg, followed by 5 μg/kg/min; group EN (esmolol + nicardipine group, n = 20) received esmolol 1 mg/kg and nicardipine 15 μg/kg, followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…[1214181920] The mean difference in emergence time between esmolol and placebo was 1.60 min (95% CI: −3.37–0.07, P = 0.07, I 2 = 89.9%); heterogeneity was noted to be high [Figure 4]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[1214181920] The mean difference in emergence time between esmolol and placebo was 1.60 min (95% CI: −3.37–0.07, P = 0.07, I 2 = 89.9%); heterogeneity was noted to be high [Figure 4]. …”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported on the use of rescue analgesics in the PACU. [ 9 11 12 13 14 ] Intravenous fentanyl was used as the rescue analgesic in four studies and intravenous infusion of tramadol along with intramuscular diclofenac was administered in one study. [ 13 ] Overall, esmolol reduced the requirement for rescue opioid by 69% [OR: 0.31, 95% CI: 0.16–0.80, P = 0.0001, I 2 = 0.0%, Figure 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations